2007
DOI: 10.1111/j.1467-9280.2007.01916.x
|View full text |Cite
|
Sign up to set email alerts
|

Putting Feelings Into Words

Abstract: Putting feelings into words (affect labeling) has long been thought to help manage negative emotional experiences; however, the mechanisms by which affect labeling produces this benefit remain largely unknown. Recent neuroimaging studies suggest a possible neurocognitive pathway for this process, but methodological limitations of previous studies have prevented strong inferences from being drawn. A functional magnetic resonance imaging study of affect labeling was conducted to remedy these limitations. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
448
6
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 908 publications
(498 citation statements)
references
References 27 publications
33
448
6
11
Order By: Relevance
“…Identify safety signals (objects, people, medication) and safety behaviors (staying near the exit, over-preparation), and wean them during exposures Salkovskis, 1991;Sloan & Telch, 2002 Linguistic processing Label emotions and stimuli during exposure Kircanski et al in press;Lieberman et al, 2007 Multiple contexts Vary the context of exposure, including specific locations, presence of others, times of day, mood states, and temporal relationship to therapy sessions. Culver et al, 2011;Mystkowski et al, 2002;Mystkowski et al, 2003;Mysktowski et al, 2006 Behavioral aid to reconsolidation Brief exposure to a CS (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Identify safety signals (objects, people, medication) and safety behaviors (staying near the exit, over-preparation), and wean them during exposures Salkovskis, 1991;Sloan & Telch, 2002 Linguistic processing Label emotions and stimuli during exposure Kircanski et al in press;Lieberman et al, 2007 Multiple contexts Vary the context of exposure, including specific locations, presence of others, times of day, mood states, and temporal relationship to therapy sessions. Culver et al, 2011;Mystkowski et al, 2002;Mystkowski et al, 2003;Mysktowski et al, 2006 Behavioral aid to reconsolidation Brief exposure to a CS (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…According to a neuroimaging study, when facing a fear-evoking situation, stronger coupling between the caudate and right ventrolateral prefrontal cortex (vlPFC) resulted in less urge and no unrealistic reactions, but stronger coupling between the caudate and sgACC resulted in greater urge and unrealistic reactions [69]. Meanwhile, the right vlPFC has been implicated in affect labeling that can reduce negative emotional responses in the amygdala [71], and the sgACC is related to fear and depression and postulated as the Depressor part of the vmPFC. Thus, MBB provides a leverage, similar to affective labeling, to name an urge-laden emotional process as an "activated Identity System" such that initial urge-like tension and racing thoughts related to a latent Requirement can be cognitively managed and, eventually, original unrealistic expectations may be updated and thus defuse the Requirement.…”
Section: Brain-based Model For Mind-body Bridgingmentioning
confidence: 99%
“…A number of neuroimaging studies have demonstrated that labeling one's emotional experience activates areas of the PFC, and reduces activation in the amygdala (Gorno-Tempini et al, 2001;Hariri, Bookheimer, & Mazziotta, 2000;Hariri, Mattay, Tessitore, Fera, & Weinberger, 2003;Narumoto et al, 2000). The right ventrolateral PFC is consistently activated during affect labeling (Cunningham, Johnson, Chris, Gore, & Banaji, 2003;Lieberman et al, 2007;Narumoto et al, 2000), and it is presumed that this region downregulates amygdala activation. The principle of neural plasticity states that repetition of a process can increase efficiency and efficacy of that process through changes in neuron function, chemical profile, and structure (Anderson, 2010;Kandel & Schwartz, 1982).…”
mentioning
confidence: 99%